First Association of Interleukin 12 Receptor Beta 1 Deficiency with Sjögren’s Syndrome - Sogkas, Georgios; Atschekzei, Faranaz; Schacht, Vivien; von Falck, Christian; Jablonka, Alexandra; Jacobs, Roland; Stoll, Matthias; Witte, Torsten; Schmidt, Reinhold E. (Frontiers in Immunology, 2017)
Introduction: Interleukin 12 receptor beta 1 (IL12Rβ1) deficiency is a primary immunodeficiency resulting mainly in susceptibility to opportunistic infection by non-tuberculous, environmental mycobacteria and severe infection caused by Salmonella spp.. Till now less than three hundred patients with IL12Rβ1 deficiency have been reported. Among them, only three have been described to develop autoimmunity. Case presentation: We present the case of a 50-year-old male with IL12Rβ1 deficiency due to compound heterozygosity (c. 1623_1624delGCinsTT (pGln542Stop) and c.1791+2T>C (donor splice site), who – 18 months after diagnosis of disseminated BCGitis – presented with recurrent fever and sicca syndrome. No indication of an infectious origin of these symptoms could be found at that point. The diagnosis of a Sjögren’s syndrome was made on the basis of fulfilled American-European consensus classification criteria, including a positive minor salivary gland biopsy. Conclusions: Apart from persistent antigenic stimulation, which may drive autoimmune inflammation in primary immunodeficiency, evidence on the involvement of IL-12 in pathogenesis of Sjögren’s syndrome suggests, that the same immunological mechanism may underlie both defense against infection and the maintenance of tolerance. To our knowledge, this is the first report of a case of autoimmunity in form of Sjögren’s syndrome in a patient with a primary immunodeficiency and one of the rare cases of IL12Rβ1 deficiency with manifested autoimmunity.